Harnessing an Artificial Intelligence Platform to Dynamically Individualize Combination Therapy for Treating Colorectal Carcinoma in a Rat Model. Issue 4 (20th November 2019) - Ding, Xianting; Chang, Vincent H. S.; Li, Yulong; Li, Xin; Xu, Hongquan; Ho, Chih‐Ming; Ho, Dean; Yen, Yun
Abstract: Designing multi‐drug regimens often involves target‐ and synergy prediction‐based drug selection, and subsequent dose escalation to achieve the maximum tolerated dose (MTD) of each drug. This approach may improve efficacy, but not the optimal efficacy and often substantially increases toxicity. Drug interactions depend on many pathways in the omics networks and further complicate the design process. The virtually infinite drug–dose parameter space cannot be reconciled using conventional approaches, which are largely based on prediction. This barrier at least partially accounts for the low response rates that are observed with conventional mono‐ and combinatorial chemotherapy. A combination of nonstandard therapies for colorectal cancer (AGCH: adriamycin, gemcitabine, cisplatin, and herceptin) at ¼ MTD is used to treat the rats, the tumor response rates varied in a wide range. Some of the tumor response rates are close to that of control group. This work harnesses an artificial intelligence (AI) platform that is mechanism free and can dynamically optimize combinatorial therapy in rats. The individually optimized AGCH regimen reveal starkly different drug–dose parameters, which can converge each rat toward the same and low tumor response rate. Importantly, this AI‐based drug–dose optimization technology is an actionable platform, which can achieve N‐of‐1 therapy. Abstract : This work harnesses an artificial intelligence (AI) platform that is mechanism free and can dynamically optimize combinatorial colorectal carcinoma therapy in rats. The individually optimized regimen reveals starkly different drug–dose parameters, which can converge each rat toward the same low tumor response rate.